CP-042 Inappropriate drug prescriptions and associated factors in Nursing Homes. (24th February 2014) - Cool, C; Lebaudy, C; Rouch, L; Rolland, Y; Lapeyre-Mestre, M; Cestac, P
Abstract : Background: Older people residing in nursing homes (NHs) often suffer from several comorbid conditions and cognitive and functional decline. Polymedication is frequent in this population, increasing the risk of inappropriate prescribing, which leads to adverse drug-related events such as falls and hospitalisation. This drug-related ill-health has significant socio-economic consequences and has been declared a public health priority. However, the prevalence of inappropriate prescribing remains high. We hypothesised that inappropriate prescribing was associated with individual characteristics, but also with structural and organisational factors within NHs. Purpose: To identify inappropriate prescribing and associated structural and organisational factors among NH residents. Materials and methods: This cross-sectional study was conducted within a representative sample of the French IQUARE study. We checked residents' drug prescriptions. Inappropriate prescribing was defined using a specific indicator, based on the Summary of Product Characteristics and the Laroche list, and taking into account all available clinical data. It was defined by the presence of at least one of the following criteria: drug with unfavourable benefit/risk ratio, absolute contraindication and significant drug-drug interaction. Associated factors were identified using a multivariate logistic regression model. Results: Of the 974 residents included, 71% had been prescribed inappropriate treatment, mainly patients without a diagnosis of dementia, with numerous comorbid conditions and taking several medicines, with 9 drugs on average. The classes most involved in inappropriate prescribing were long half-life benzodiazepines, proton pump inhibitors, antipsychotics and cerebral vasodilators. After adjustment, age (OR = 1.02; 95% CI [1.00–1.04]), number of comorbid conditions (OR1/0 = 1.22; 95% CI [0.85–1.74] and OR2/0 = 1.72; 95% CI [1.23–2.41]) and a re-evaluation of prescribing since entry into the NH (OR = 1.45; 95% CI [1.07–1.96]) were associated with an increased risk of inappropriate prescribing. By contrast, dementia was associated with a lower risk (OR = 0.70; 95% CI [0.53–0.94]). Among the structural and organisational characteristics of NHs, only access to a psychiatric opinion and/or to a psychiatric hospitalisation was associated with inappropriate prescribing. Conclusions: Our work finds that individual characteristics, but also NH organisation-related factors such as access to a psychiatric opinion and/or to a psychiatric hospitalisation are associated with inappropriate prescribing in NH residents. No conflict of interest.